Features of business ecosystems promotion - K. A. Arzhanova; A. S. Kachalova (Вестник университета, 2024)
The article is devoted to the tools for promoting business ecosystems in Russia in 2023.   The purpose of the study is to determine the tools.   The methodological basis of this study was formed by the main works on business and business ecosystems promotion. In the course of the research, the follo wing sources were examined: the Internet resources of Russian companies and the object in question, mass media sources in the field of marketing, advertising and public relations, as well as the works of Russian and foreign authors. The main tools of business promotion with the help of geo-services, influencers, and electronic mail are considered, and their features, application specifics are described. The following directions that Russian business ecosystems are already using to promote their goods and services are analysed: management of their own media, large-scale rebranding, which affects positioning and visual component, holding various events aimed at achieving a company’s goals. The article also predicts the direction of trends in business ecosystems promotion. They can be included by new business ecosystems when building their own marketing strategy. Further research in this field may be connected to work on determining the stages of business ecosystems promotion, understanding how this can be done with consideration to the specificity of a particular company.